Meena Shorey: The Droll Queen of Partition - Siddique, Salma (BioScope: South Asian Screen Studies, 2015)
This article is a star study of actress Meena Shorey, whose career navigated the tortuous itinerary of a divisive decolonization, travelling amongst cities and nations, identities and communities, and refugees and citizens. Becoming famous as the “droll queen,” Meena appeared in a number of romantic comedies in post-Partition Bombay, which were directed by her husband and refugee filmmaker Roop K. Shorey, and loosely modeled on the Hollywood screwball. With unconventional gender dynamics and Meena as the ultimate star of these comedies, I argue that the Shorey films were sublime renderings of Partition social relations fissured along community and gender. Ek Thi Ladki (1949), in particular, is a Partition screwball that carries the historic imprint through a cynical humor, the nostalgia for Lahore and the reorientations of national perspectives. As the interfaith romance and marriage between a Muslim Meena and a Hindu Roop constituted a utopian alliance that informed the circulation of these films, it also served as a discursive site for communal and national tensions. Using archival sources accessed in both India and Pakistan, including Meena’s memoir, the article recovers the productive cosmopolitanism that characterized the short-lived Meena–Roop collaboration, which ended with the actress’s migration to Pakistan.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wOTc0OTI3NjE1NTg2OTMx